STUDY OF THE PHENOMENON OF LOVE IN 20TH CENTURY ENGLISH LITERATURE - Kimsanova, Rahnamo Solijonovna; Abbasova, Nargiza (INTERNATIONAL CONFERENCES, 2022)
The release of Wordsworth and Coleridge’s Lyrical Ballads and the passing of author Sir Walter Scott are considered the beginning and conclusion of the Romantic Period in English literature, respectively. A longer time period was covered by the historical and literary backgrounds and impacts. In this article, there are given main information about love in 20th century.